Lenovo signs agreement with PIF subsidiary Alat for $2bn in bonds. - Aguinaldo, Jennifer (MEED Business Review, 2024)
Lenovo Group, a Hong Kong-based company, has signed an agreement with Alat Enate, a subsidiary of Saudi Arabia's Public Investment Fund (PIF), to issue $2 billion in zero-coupon convertible bonds. The funds will be used to repay debt, supplement working capital, and for general corporate purposes. Additionally, Lenovo plans to establish a regional headquarters in Riyadh, Saudi Arabia, which will include research and development centers and manufacturing facilities for computers and servers. This partnership is part of Saudi Arabia's goal to become a global hub for electronics and advanced industries.